Hamz and facilitation in satire poetry in the Umayyad era (Audio study) - Abdul-Ridha Al-Obaidi, Researcher; Mohamed Mezal Khalati, Prof. Dr. (lark, 2022)
This research is a presentation on the notion of hamz and facilitation during the Umayyad era, and I discovered that Umayyad poets addressed these two occurrences. In reality, the hamz and the facilitator are both well-known languages. It is also evident that it is attributed to his tribes, as the Quraish did not achieve the hamz and others did; the investigation is the original and the mitigation is approving; and what is attributed to Quraysh may be an exaggeration, as the hamz was mentioned in their poetry and he observed their correct prose. He: The Quraish do not utter some words, not all of them, such as: (ras, wafas, wafar, and a wabir), and this of course does not include their eloquence like the Prophet and his family, who are the most eloquent Arabs. The Prophet (PBUH), said: (I am the most eloquent of the Arabs, but I am from Quraysh) - meaning because I am from Quraysh - and what is mentioned in the collections of their poets such as the Diwan of Abu Talib, the Diwan of Imam Ali (peace be upon him) and the Diwan of Hassan bin Thabet is sufficient to prove that the Quraysh She was humming, but this idea - the idea that Quraysh do not murmur - has prevailed over many unaudited researchers. Al-Farabi states that the Quraish are the best among the Arabs at picking the most eloquent terms, hence it is improper for them to substitute facilitation for hamz or vice versa. Some of them who lacked eloquence were facilitating what was generally neglected by the tribes, and some Arab tribes occasionally exaggerated in the hamz of some words, including some of Tamim, and some surrounding tribes who are deep in the Bedouin, and they mumble the unmarried (like the jinn), they say (the elves).
Keywords: The hamz, the realization of the hamz, the exaggeration of the hamz, the mitigation of the hamz, the facilitation.